Hubungkait model gaya pembelajaran kolb-dunn dengan pencapaian akademik pelajar program sains kognitif - Roseliza, Binti Abdul Kadir. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Generally, this project aims to perfprm a preliminary illvestigation into the relationship between KolbDunn Learning Style and academic achievemellt of Cognitive Science Program Studellt in UNIMAS. This project also aims to find the best learning style that significant with excellent academic achievement.